Vivianite as an important iron phosphate precipitate in sewage treatment plants. (1st November 2016) - Wilfert, P.; Mandalidis, A.; Dugulan, A.I.; Goubitz, K.; Korving, L.; Temmink, H.; Witkamp, G.J.; Van Loosdrecht, M.C.M.
Abstract: Iron is an important element for modern sewage treatment, inter alia to remove phosphorus from sewage. However, phosphorus recovery from iron phosphorus containing sewage sludge, without incineration, is not yet economical. We believe, increasing the knowledge about iron-phosphorus speciation in sewage sludge can help to identify new routes for phosphorus recovery. Surplus and digested sludge of two sewage treatment plants was investigated. The plants relied either solely on iron based phosphorus removal or on biological phosphorus removal supported by iron dosing. Mössbauer spectroscopy showed that vivianite and pyrite were the dominating iron compounds in the surplus and anaerobically digested sludge solids in both plants. Mössbauer spectroscopy and XRD suggested that vivianite bound phosphorus made up between 10 and 30% (in the plant relying mainly on biological removal) and between 40 and 50% of total phosphorus (in the plant that relies on iron based phosphorus removal). Furthermore, Mössbauer spectroscopy indicated that none of the samples contained a significant amount of Fe(III), even though aerated treatment stages existed and although besides Fe(II) also Fe(III) was dosed. We hypothesize that chemical/microbial Fe(III) reduction in the treatment lines is relatively quick and triggers vivianite formation. Once formed, vivianite may endure oxygenated treatment zones due to slow oxidation kinetics and due to oxygen diffusion limitations into sludge flocs. These results indicate that vivianite is the major iron phosphorus compound in sewage treatment plants with moderate iron dosing. We hypothesize that vivianite is dominating in most plants where iron is dosed for phosphorus removal which could offer new routes for phosphorus recovery. Highlights: Fe chemistry and its correlation with P in two sewage treatment plants (STPs) was studied. Surplus and digested sludge solids in the investigated STPs were dominated by Fe(II). The Fe(II)P mineral vivianite was a major iron compound in all samples. We hypothesize: Vivianite is a key compound in all STPs and offers new P recovery routes.